Frequency responses of graded-gap GaInAs- based structure with impact ionization - Боцула, О. В.; Приходько, К. Г.; Шевченко, О. Р. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
The kinetic processes in the triple semiconductor compound Ga z In 1-z As are considered in the conditions of electron initiated impact ionization. An analysis of the diode operating was carried out using the Monte Carlo method, taking into account the coordinate dependence of all semiconductor parameters. The impact ionization parameters of homogeneous Ga z In 1- z As compounds were determined depending on the Ga content and in heterogeneous structures with different laws of its spatial distribution. The comparative analysis of obtained parameter was carried out. The time delay intervals of the impact ionization development is shown to correspond to the terahertz frequencies range, and impact ionization in the graded band semiconductors can be used for generation obtaining in this range.